A Note on Semialgebraically Proper Maps - Park, Dae Heui (Ukrains’kyi Matematychnyi Zhurnal, 2014)
We prove that a semialgebraic map is semialgebraically proper if and only if it is proper. As an application of this assertion, we compare the semialgebraically proper actions with proper actions in a sense of Palais.